LncRNA GAS5 contributes to lymphatic metastasis in colorectal cancer - Zheng, Yongbin (Oncotarget, 2016)
Colorectal cancer (CRC) ranks the third most common type of cancer worldwide. However, the detailed molecular mechanisms underlying these processes are poorly understood. Recent studies have shown that lncRNAs play important roles in carcinogenesis and progression of CRC. The lncRNA growth arrest special 5 (GAS5), was previously identified to be down-regulated and functions as a tumor suppressor gene in many kinds of cancers. In current two-stage, case-control study, we systematically evaluated the potential role of lncRNA GAS5 and its genetic variation rs145204276 in the development and metastasis process of CRC in a Chinese population. We found the allele del of rs145204276 was significantly associated with 21% decreased risk of CRC (OR=0.79; 95% CI=0.70-0.89; P value = 5.21×10(−5)). Compared with the genotype ins/ins, both the genotype ins/del (OR=0.78; 95% CI=0.68-0.91) and del/del (OR=0.64; 95% CI=0.49-0.84) showed decreased susceptibility. For both in colon and rectum cancers, the associations kept statistically significant (OR=O.78 and 0.80, while P value = 4.56×10(−4), and 3.80×10(−3), respectively). The results also showed that the carriers of allele del are less likely to get lymph node metastasis (OR=0.80; 95% CI=0.68-0.95; P value = 0.010). Taken together, our findings provided strong evidence for the hypothesis that GAS5 rs145204276 were significantly associated with the susceptibility and progression of CRC.